1999
DOI: 10.1046/j.1469-8137.1999.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐colonization of Scots pine (Pinus sylvestris) seedlings by the ectomycorrhizal fungus Paxillus involutus in the presence of inhibitory levels of Cd and Zn

Abstract: The effects of Cd and Zn on cross-colonization by Paxillus involutus of Scots pine seedlings was examined by using pairs of ectomycorrhizal (ECM) and non-mycorrhizal (NM) seedlings grown in the same vessel. This was done to assess, first, the ability of P. involutus to colonize NM Scots pine seedlings by growth from colonized roots of other Scots pine seedlings in the presence of Cd or Zn, and, second whether ECM colonization of Scots pine by P. involutus provided a competitive advantage over NM seedlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The data indicate that mycorrhization efficiency may depend on specific interactions between fungal species and associated bacteria. Moreover, root colonization is determined by recognition and compatibility between plant host and fungus (Hartley et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data indicate that mycorrhization efficiency may depend on specific interactions between fungal species and associated bacteria. Moreover, root colonization is determined by recognition and compatibility between plant host and fungus (Hartley et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…After germination, the root systems of the seedlings were dipped in the bacterial suspensions for 20 min followed by transferring of the seedlings to polyethylene pots containing 150 g of autoclaved soil, prepared according to Kawai (1997), thoroughly mixed with fungal inoculum in ratio 15:1 (v/v). In total, 80 plants, one seedling per pot, were kept in a plant growth cabinet with a 14 h photoperiod (daylight Pine mycorrhization against Cd(II) impact 451 supplemented with artificial light), 70% relative humidity, and day and night temperatures of 23°C and 18°C (Hartley et al 1999), respectively for 3 months. The seedlings were wetted with water within first 2 weeks, then they were wetted twice a week (100 ml) with Cd(II) as CdCl 2 at concentration of 10 lg Cd(II) ml -1 .…”
Section: Plant Growth Conditions and Experimental Designmentioning
confidence: 99%
“…A laboratory experiment of Hartley et al (1999) suggests that there is only a minor difference in Zn and Cd sensitivity of Scots pine and its mycobiont Paxillus involutus. In Lommel, the pine trees were able to establish because of the application of soil additives in the planting holes.…”
Section: mentioning
confidence: 99%
“…The role that ECM fungi play in the metal sensitivity of plants, however, is less clear [4]. Some authors report that ECM fungi confer tolerance to their host plants [1, 18], whereas others report that the beneficial effect of ECM colonization is equal in both normal and contaminated environments [11, 19]. Results from this study show that Cd and Zn are more toxic to ECM fungal infection than to Scots pine seedlings themselves, with minimal effects on shoot biomass and total root‐tip density and a lesser effect on root biomass than on ECM infection levels.…”
Section: Discussionmentioning
confidence: 99%
“…Successions of ECM fungi on plant roots rely on cross‐colonization from other plant roots or on colonization from propagules in the soil [10]. A recent study of ECM Scots pine showed that whereas cross‐colonization from one plant to another can occur in the presence of Cd and Zn for single ECM fungal isolates in vermic‐ulite culture, the process is partially inhibited by both metals [11].…”
Section: Introductionmentioning
confidence: 99%